A comparison of two hydrogen storages in a fossil-free direct reduced iron process. (13th August 2021) - Andersson, Joakim; Grönkvist, Stefan
Abstract: Hydrogen direct reduction has been proposed as a means to decarbonize primary steelmaking. Preferably, the hydrogen necessary for this process is produced via water electrolysis. A downside to electrolysis is the large electricity demand. The electricity cost of water electrolysis may be reduced by using a hydrogen storage to exploit variations in electricity price, i.e., producing more hydrogen when the electricity price is low and vice versa. In this paper we compare two kinds of hydrogen storages in the context of a hydrogen direct reduction process via simulations based on historic Swedish electricity prices: the storage of gaseous hydrogen in an underground lined rock cavern and the storage of hydrogen chemically bound in methanol. We find the methanol-based storages to be economically advantageous to lined rock caverns in several scenarios. The main advantages of methanol-based storage are the low investment cost of storage capacity and the possibility to decouple storage capacity from rate capacity. Nevertheless, no storage option is found to be profitable for historic Swedish electricity prices. For the storages to be profitable, electricity prices must be volatile with relatively frequent high peaks, which has happened rarely in Sweden in recent years. However, such scenarios may become more common with the expected increase of intermittent renewable power in the Swedish electricity system. Graphical abstract: Image 1 Highlights: Storage of H2 key to lower costs of hydrogen-based steelmaking. Storage of compressed H2 and H2 bound in methanol compared. H2 storage in methanol integrates well in hydrogen direct reduction process. Simulations using historic electricity prices favor methanol in several scenarios. Low-cost storage capacity, flexibility of sizing main advantages of methanol.